Pengaruh Debt to Equity Ratio dan Biaya Produksi Terhadap Pertumbuhan Laba (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the variables of debt to equity ratio (DER), and production costs on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data used are secondary data sourced from the company's financial reports obtained from the Indonesia Stock Exchange website and the company's official website. The population in this study were food and beverage sub-sector companies listed on the IDX for the 2019-2023 period with 49 companies. The research sample used a purposive sampling method of 24 companies. The results of the study showed that partially, DER had a significant effect on profit growth in a negative direction, which means that the higher the DER, the company's profit growth tends to decrease. Meanwhile, production costs did not have a significant effect on profit growth. This study provides implications for companies in managing a balanced capital structure and the importance of production cost efficiency even though it indirectly affects profit growth.